Discouraging factors in knowledge sharing in software development teams - Varcok, Tomas (2020)
Knowledge sharing has a crucial role in intellectual work such as software development. Intellectual capital in form of specialized knowledge, skills, and expertise belong to the most valuable resources that software development organizations possess. The ability to manage and apply knowledge correctly can result in an important competitive advantage. There appears to be a wide agreement on the high importance of managing and sharing knowledge within teams among practitioners. Interestingly, this importance does not seem to be reflected in practicing knowledge sharing in real environments, which often leads to major problems such as lower work efficiency, weaker cooperation, failing to utilize the full potential of available knowledge, and losing valuable knowledge exclusively owned by leaving individuals. This thesis argues that it is important to identify the reasons behind this gap. The aim is to identify the discouraging factors – the issues that obstruct knowledge sharing and lower its quantity and quality. Additionally, the thesis seeks to identify how the influence of these discouraging factors could be reduced or eliminated. Due to the explorative nature of the study, the selected research approach is an interpretive case study. The qualitative data were collected during semi-structured interviews with ten participants holding different professional roles in three different teams within one Nordic software development organization. The premise of the study was confirmed as the data show that there truly is a gap between how important practitioners see knowledge sharing, and how much it is reflected in their regular work. The reasons for this gap were identified in form of multiple discouraging factors, the most noticeable ones being the Perceived difficulty, Lack of attention, Insufficient or incorrect encouragement, and Missing systematic approach. Practitioners can benefit from this study by understanding what is hindering knowledge sharing in their teams. The thesis offers several suggestions on how practitioners can overcome these obstacles. The main recommendations are to pay more attention to knowledge sharing, lower its perceived difficulty, and integrate it into the existing processes and practices in a concrete executable form.